(3fgGjI GdENJUGQ aj GdaQGFVs - (3chTjGQ Hf dHGf GdLjdj, CHh GdMSf,J (B350 (3g` s
(3ChdgG (B:s
(3bGd GdTjN OYGfi bhd GdfHi Udi Gddg Ydjg hSde (B( (3JYdehG GdaQGFV aEfgG ef Ojfce (B) (3ai GNJUGQ aQhYg HGH GdaQhV s
(3BNQgG (B:s
(3HGH GdhdGA s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B148 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B838s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3Yde GdaQGFVs